The role of peroxisome proliferator-activated receptors in the tumor microenvironment, tumor cell metabolism, and anticancer therapy - Sun, Jiaao; Yu, Liyan; Qu, Xueling; Huang, Tao (Frontiers in Pharmacology, 2023)
Peroxisome proliferator-activated receptors (PPARs) have been extensively studied for over three decades and consist of three isotypes, including PPARα, γ, and β/δ, that were originally considered key metabolic regulators controlling energy homeostasis in the body. Cancer has become a leading cause of human mortality worldwide, and the role of PPARs in cancer is increasingly being investigated, especially the deep molecular mechanisms and effective cancer therapies. PPARs are an important class of lipid sensors and are involved in the regulation of multiple metabolic pathways and cell fate. They can regulate cancer progression in different tissues by activating endogenous or synthetic compounds. This review emphasizes the significance and knowledge of PPARs in the tumor microenvironment, tumor cell metabolism, and anti-cancer treatment by summarizing recent research on PPARs. In general, PPARs either promote or suppress cancer in different types of tumor microenvironments. The emergence of this difference depends on various factors, including PPAR type, cancer type, and tumor stage. Simultaneously, the effect of anti-cancer therapy based on drug-targeted PPARs differs or even opposes among the three PPAR homotypes and different cancer types. Therefore, the current status and challenges of the use of PPARs agonists and antagonists in cancer treatment are further explored in this review.